Physical security : 150 things you should know - Fennelly, Lawrence J., 1940- (Butterworth-Heinemann is an imprint of Elsevier, 2016)
This book covers the latest technological trends for managing the physical security needs of buildings and campuses of all sizes. Through anecdotes, case studies, and documented procedures, the authors have amassed the most complete collection of information on physical security available.